Media crossroads : intersections of space and identity in screen cultures - Matos, Angel Daniel; Massood, Paula J., 1965-; Wojcik, Pamela Robertson, 1964- (Duke University Press, 2021)
"The contributors to Media Crossroads examine space and place in media as they intersect with sexuality, race, ethnicity, age, class, and ability."--